Progress on structural modification of Tetrandrine with wide range of pharmacological activities - Mo, Liuying; Zhang, Fan; Chen, Feng; Xia, Lei; Huang, Yi; Mo, Yuemi; Zhang, Lingqiu; Huang, Daquan; He, Shunli; Deng, Jiagang; Hao, Erwei; Du, Zhengcai (Frontiers in Pharmacology, 2022)
Tetrandrine（Tet）, derived from the traditional Chinese herb Fangji, is a class of natural alkaloids with the structure of bisbenzylisoquinoline, which has a wide range of physiological activities and significant pharmacfological effects. However, studies and clinical applications have revealed a series of drawbacks such as its poor water solubility, low bioavailability, and the fact that it can be toxic to humans. The results of many researchers have confirmed that chemical structural modifications and nanocarrier delivery can address the limited application of Tet and improve its efficacy. In this paper, we summarize the anti-tumor efficacy and mechanism of action, anti-inflammatory efficacy and mechanism of action, and clinical applications of Tet, and describe the progress of Tet based on chemical structure modification and nanocarrier delivery, aiming to explore more diverse structures to improve the pharmacological activity of Tet and provide ideas to meet clinical needs.